Nature of the common good as the foundation of the community - Jasiński, Karol (Array, 2021)
The subject of interest of the author of the text is the common good as an inalienable element of the organization of the human community. The paper consists of three parts. The first part analyses the need for a common good as the basis of social and political life. The starting point was the distinction of four forms of common life (community, society, political body and state), defining the nature of society, presentation of three forms of relationship between man and society (individualism, collectivism and personalism) and identifying problems related to the definition of the common good. In the second part, the author presented a reflection on the procedural common good in the liberal tradition, the issue of impartiality and identification of the common good in the process of the debate. In the third part, attention is paid to the personalistic view of the common good, which is based on the integral development of personal human nature in the framework of the appropriate institutions and structures. This understanding of the common good is, in the author’s conviction, the best point of reference in social and political life.